Factors influencing a customer intention to participate in family takaful among teachers in Kuah, Langkawi - Afiffatul Afiffah, Abdul Rahman (2021)
Family Takaful is one of the protection for financial urgent in event of accident. Family Takaful was introduced in Malaysia in year 1984. The development of the Family Takaful products in Malaysia are more than 20 products, that give opportunity to create awareness to among public people and encourage potential customers to participate in Family Takaful products. Therefore, the purpose of this research is to explore the Factors that Influence Customers Intention to Participate in Family Takaful among Teachers in Kuah, Langkawi. The first objective is to identify the differences between selected demographic factors influencing customers' intention to participate in the Family Takaful. The second objective is to analyze the relationship between selected factors toward customers' intention to participate in the Family Takaful. The third objective is to determine the most influencing customers' intention to participate in the Family Takaful. The methodology used in this study is the quantitative method with questionnaires development in assessing the Intention of Customers to Participate in Family Takaful among Teachers. The underpinning theory is using Theory of planned behavior (TPB) and the supported theory is Technology Acceptance Model Theory (TAM model). The unit of analysis for respondents is teachers in Kuah, Malaysia. The correlation analysis was analyzed using Pearson Correlation coefficient analysis. After that, the causal relationship was analyzed using multiple regression analysis. The finding in this study indicates that Cronbach’s alpha statistical test for measuring internal reliability is larger than 0.8 for all four variables. Therefore, four constructs exhibit good reliability that indicates the suitability of internal consistency. The outcome of the correlation between all independent variables with dependent variables are higher than 0.6 and above. Next, The coefficient of determination or R-squared value of 0.661 indicates 66.1% of the variation in customer intention. Moreover, it is clear that there is a strong and positive relationship between all independent variables towards the dependent variable. In regression test presented has only three of four factors that are significant on the intention of customer to participate in Family Takaful, that are a Subjective Norm, Perceived Ease of Use, and Attitude. Meanwhile, Perceived Behavioral Control that is not significant with the dependent variable. The implication of this study is to contribute to the theoretical, giving idea to markerter in Takaful industry and future academician as a reference to develop new idea and new research give impact to Takaful industry.